STUDI TENTANG KERAJINAN KAMPIA EMBUN PAGI KECAMATAN MATUR KABUPATEN AGAM - PUSPITA ANGGREANI, Drs. Erwin, M.Sn, Drs. Efrizal, M.Pd (Serupa The Journal of Art Education, 2014)
This study aims to knowing of product forms, making techniques,and motif be found on the Kampia product in Embun Pagi subdistrictof Matur Agam. The research subject is Kampia craft inEmbun Pagi sub-district of Matur, Agam with research method wasqualitative descriptive. Based on the results of research in the fieldcan be concluded: 1) Kampia product produced in Embun Pagibasically have three dimensional form, such as Kampia of twocorner, six corner, and manggis Kampia. 2) There were startingtechniques, forming, and finishing on the Kampia product. 3) Motifthat is created from the combination of each technique and thedifference of color ribbons from warp and weft can be generate tovarious forms of interesting motif depending on the creativity ofartisansKata Kunci: Kerajinan Kampia, Bentuk, Teknik, Motif